The Effect of Oral Vaccination with Mycobacterium bovis BCG on the Development of Tuberculosis in Captive European Badgers (Meles meles) - Chambers, Mark A.; Aldwell, Frank; Williams, Gareth A.; Palmer, Si; Gowtage, Sonya; Ashford, Roland; Dalley, Deanna J.; Davé, Dipesh; Weyer, Ute; Salguero, Francisco J.; Nunez, Alejandro; Nadian, Allan K.; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
The European badger (Meles meles) is a reservoir host of Mycobacterium bovis and responsible for a proportion of the tuberculosis (TB) cases seen in cattle in the United Kingdom and Republic of Ireland. An injectable preparation of the bacillus Calmette-Guérin (BCG) vaccine is licensed for use in badgers in the UK and its use forms part of the bovine TB eradication plans of England and Wales. However, there are practical limitations to the widespread application of an injectable vaccine for badgers and a research priority is the development of an oral vaccine deliverable to badgers in bait. Previous studies reported the successful vaccination of badgers with oral preparations of 108 colony forming units (CFU) of both Pasteur and Danish strains of BCG contained within a lipid matrix composed of triglycerides of fatty acids. Protection against TB in these studies was expressed as a reduction in the number and apparent progression of visible lesions, and reductions in the bacterial load and dissemination of infection. To reduce the cost of an oral vaccine and reduce the potential for environmental contamination with BCG, it is necessary to define the minimal efficacious dose of oral BCG for badgers. The objectives of the two studies reported here were to compare the efficacy of BCG Danish strain in a lipid matrix with unformulated BCG given orally, and to evaluate the efficacy of BCG Danish in a lipid matrix at a ten-fold lower dose than previously evaluated in badgers. In the first study, both BCG unformulated and in a lipid matrix reduced the number and apparent progression of visible lesions and the dissemination of infection from the lung. In the second study, vaccination with BCG in the lipid matrix at a ten-fold lower dose produced a similar outcome, but with greater intra-group variability than seen with the higher dose in the first study. Further research is needed before we are able to recommend a final dose of BCG for oral vaccination of badgers against TB or to know whether oral vaccination of wild badgers with BCG will significantly reduce transmission of the disease.